Bifunctional doped transition metal CoSSeNi–Pt/C for efficient electrochemical water splitting. (1st May 2022) - Deng, Wei; Gai, Yuping; Li, Dan; Chen, Zhide; Xie, Wenshuo; Yu, Jun; Yang, Renqiang; Bao, Xichang; Jiang, Fei
Abstract: Reasonable design and synthesis of hetero atom metal coordination compounds on the atomic scale can significantly improve the performance of the catalysts. Herein, Pt/C (20%) is doped and inserted into the CoSSeNi catalyst through two steps of hydrothermal reaction and high temperature calcination process. Compared with the single metal Pt/C doped CoSSe–Pt/C, the bimetal doped CoSSeNi–Pt/C can greatly enhance the hydrogen evolution reaction (HER) activity. The optimized Pt content in CoSSeNi–Pt/C is 2.25 wt%, which achieves the optimal HER and OER activity. The OER and HER overpotentials of CoSSeNi–Pt/C-0.3 nanosheets at 10 mA cm −2 only required 295 mV and 180 mV, respectively. During the accelerated durability test, in the presence of Pt/C dopants, CoSSeNi–Pt/C catalyst exhibited excellent long-time durability in alkaline media. Meanwhile, CoSSeNi–Pt/C showed much higher DOS near the Fermi level and the higher electron density near the Fermi level would facilitate the adsorption of adsorbates. Highlights: Pt/C (20%) doped and inserted into CoSSeNi catalyst. Two steps of hydrothermal reaction and high temperature calcination process. Much higher DOS near the Fermi level would facilitate the adsorption of adsorbates.